The Effectiveness of Recitation Al-Qur’an Intervention and Deep Breathing Exercise on Improving Vital Sign and anxiety Level among Congestive Heart Failure (CHF) Patients - Yudi Herdiana; Ta’adi Ta’adi; Masrifan Djamil (Alta Dharma Publisher, 2021)
Congestive heart failure (CHF) is a non-communicable disease caused by failure to pump blood. An alternative treatment with complementary therapies, such as recitation Al-Qur'an intervention and deep breathing exercise, improved oxygen saturation, and anxiety levels CHF patients. This study aimed to examine the effectiveness of recitation Al-Qur'an intervention and deep breathing exercises on strengthening the vital signs (oxygen saturation) and anxiety level among patients with congestive heart failure (CHF). The true experimental study approach post-test only with a control group design was applied in this study. Forty congestive heart failure (CHF) patients were selected through simple random sampling. The intervention group received the recitation Al-Qur'an therapy and deep breathing exercise, while the control group only received the medical treatment according to hospital standards. The findings showed that the intervention group was better on oxygen saturation and lowering anxiety levels than the control group (p-value = <0.05). In conclusion, recitation Al-Qur'an intervention and deep breathing exercises are useful to increase oxygen saturation and lowering anxiety levels in patients with congestive heart failure (CHF). This study can be used as a source for further research with larger sample size and better control over medical therapy